TEACHING ENGLISH PROFESSIONAL WRITING TO STUDENTS OF DESIGN AND FINE ARTS - Tytun, O. L.; Boichuk, A. P.; Sivkovych, H. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the problem of teaching students of Design and Fine Arts to write texts for professional purposes. The authors consider modern methods and activities for teaching writing. The authors underline the role of writing in teaching a foreign language that has gradually increased and considered as a reserve for improving the efficiency of teaching a foreign language. Stress is done on the importance for every educated modern person to produce different kinds of written texts for professional purposes. Modern advances in the field of information and communication technologies and the enormous popularity of using various social networks changed the attitude to writing. The importance of using information and communication technologies in teaching writing is considered. The authors suggest the following activities for improving and developing the acquired at school skills for writing texts. To improve the skills of writing annotations exercises are recommended. Activities for writing reports on videos are suggested. To master the skills of describing photos or paintings it is recommended to visit some sites. The authors recommend to make presentations on the given subjects. All the activities were successfully tested at English classes.